Perancangan Rak Penyimpanan Oli untuk Meningkatkan Kapasitas Warehouse - Mazidah Alfarah Syawalyah; Bayu Wiro Karuniawan; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
UT Surabaya has a warehouse for storing spare parts needed either during heavy equipment maintenance work or customer demand in purchasing spare parts. This warehouse still does not maximize the existing capacity, seen from the many spare parts that are not arranged. This is due to the lack of shelf storage capacity due to the demand for many spare parts. In addition, the placement of spare parts that are not organized according to their group creates one of the problems, namely oil leaks that hit other spare parts. Seeing these problems, it is necessary to design a warehouse rack supported using the Ulrich Method by making three design concepts for selecting the most appropriate concept and in accordance with warehouse needs. Making design and structural strength analysis using Fusion 360 Software based on Finite Element Methods. The selected concept is design concept 2 with structural strength analysis of the rack frame obtained the results of allowable deformation of 1.37 mm for manual calculation and software displacement analysis obtained the maximum value that occurs 0.3670 mm with ASTM A36 material deformation allowance of 23.87 mm. The maximum stress value of 45.82 MPa in software analysis and 45.64 Mpa in manual calculations with ASTM A36 material allowable stress limit of 166.667 MPa. Then the maximum safety factor value of 5 is obtained, which means the machine frame is safe to use. total